Dynamic data integrity auditing for secure outsourcing in the cloud. (21st March 2017) - Wei, Jinxia; Zhang, Ru; Liu, Jianyi; Li, Jing; Niu, Xinxin; Yao, Yuangang
Summary: Cloud servers provide cloud users with storage service and allow cloud users to access their files anytime. To guarantee security of the stored files, auditors need to periodically verify data block correctness. In the existing integrity verification schemes, there are few protocols to support the users' identity anonymity and the data block dynamic operation simultaneously. In this paper, we present an efficient and anonymous identity‐based integrity auditing protocol, which supports data dynamic operation and can be extended to support batch auditing in the multifile or multiuser setting. Our scheme not only resists forgery, replace, and replay attacks but also maintains users' anonymity, which is not discussed in other related techniques. The computation efficiency of auditor is improved a lot. Comparing with Zhang's efficient identity‐based public auditing scheme, our scheme is more suitable for actual application scenario with large‐scale storage system.